2y(y+5)=48

Divide each term in 2y(y+5)=48 by 2.

2y(y+5)2=482

Simplify 2y(y+5)2.

Cancel the common factor of 2.

Cancel the common factor.

2y(y+5)2=482

Divide y(y+5) by 1.

y(y+5)=482

y(y+5)=482

Apply the distributive property.

y⋅y+y⋅5=482

Simplify the expression.

Multiply y by y.

y2+y⋅5=482

Move 5 to the left of y.

y2+5y=482

y2+5y=482

y2+5y=482

Divide 48 by 2.

y2+5y=24

y2+5y=24

Move 24 to the left side of the equation by subtracting it from both sides.

y2+5y-24=0

Consider the form x2+bx+c. Find a pair of integers whose product is c and whose sum is b. In this case, whose product is -24 and whose sum is 5.

-3,8

Write the factored form using these integers.

(y-3)(y+8)=0

(y-3)(y+8)=0

If any individual factor on the left side of the equation is equal to 0, the entire expression will be equal to 0.

y-3=0

y+8=0

Set the first factor equal to 0.

y-3=0

Add 3 to both sides of the equation.

y=3

y=3

Set the next factor equal to 0.

y+8=0

Subtract 8 from both sides of the equation.

y=-8

y=-8

The final solution is all the values that make (y-3)(y+8)=0 true.

y=3,-8

Solve using the Square Root Property 2y(y+5)=48